2014
DOI: 10.1144/sp406.12
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale X-ray tomography analysis of carbonate porosity

Abstract: International audienceThe porosity (from values of <1% up to more than 50%, with a mean value of 36.5%) and permeability (from very low values to 20.4 D, with a mean value around 800 mD) of 38 plugs, with a diameter 40 mm, have been measured. These plugs were taken approximately every 1.5 m along a 100 m-long core, sampling a series of reefal carbonate platform lithofacies. A non-unique relationship between porosity and permeability is obtained. In addition, the porosity was measured from processing X-ray micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…However, more than 50% of the world's remaining oil reserves are located in carbonate reservoirs (27), and carbonate aquifers supply water wholly or partially to one quarter of the global population (28). Carbonates rocks can have complex multiscale pore structures, which render the application of X-ray μCT more challenging because of the need to select a representative sample that is small enough to achieve high resolutions on μCT images but that also captures the essential heterogeneities of the pore structure (29,30).…”
mentioning
confidence: 99%
“…However, more than 50% of the world's remaining oil reserves are located in carbonate reservoirs (27), and carbonate aquifers supply water wholly or partially to one quarter of the global population (28). Carbonates rocks can have complex multiscale pore structures, which render the application of X-ray μCT more challenging because of the need to select a representative sample that is small enough to achieve high resolutions on μCT images but that also captures the essential heterogeneities of the pore structure (29,30).…”
mentioning
confidence: 99%
“…Hebert et al (2014) demonstrate that porosity-permeability relationships that have been identified in carbonates using X-ray CT are non-unique and depend on the resolution of the X-ray CT scanner as well as the sample size. Furthermore, they demonstrate how variability in connectivity at fine scales may be obscured by connectivity measurements at larger scales.…”
Section: Selected Advancesmentioning
confidence: 87%
“…In particular, the amount of microporosity and the way that micro-and macroporosity are connected in carbonates appears to impact capillary pressure and relative permeability curves (Jiang et al 2013a, b). It is now possible to quantitatively combine pore-scale modelling studies, such as those of Prodanović et al (2014) or Jiang et al (2013a, b), with multiscale X-ray CT imaging of carbonates, as represented by Hebert et al (2014). By analogy to probabilistic model concepts developed in hydrology for single-phase flow, the quantitative insights from pore-scale studies can also be used to develop probabilistic models for multiphase flow that link the variability in porescale physics to the Darcy scale.…”
Section: Selected Advancesmentioning
confidence: 99%
“…In 2014, Ma et al [217] proposed a multiscale digital core-reconstruction method for shale gas rocks. Hebert et al [218] employed a multiscale method to evaluate the porosity of carbonate rocks. In 2015, Yang et al [219] proposed a method for combining smallscale digital cores that is equivalent to converting the resulting 3D digital cores into larger-scale 3D digital cores.…”
Section: D Slicementioning
confidence: 99%